Comparison of feeding habits and habitat use between invasive raccoons and native raccoon dogs in Hokkaido, Japan - Osaki, Aya; Sashika, Mariko; Abe, Go; Shinjo, Kohei; Fujimoto, Ayako; Nakai, Mariko; Shimozuru, Michito; Tsubota, Toshio (BMC ecology, 2019)
In Japan, invasive raccoons cause severe ecological and social problems by transmitting pathogens to humans, livestock, and native species, causing substantial crop damage, and competing with native species. Possible competition between invasive raccoons and native raccoon dogs is of concern in Japan because Japanese raccoon dogs have a limited distribution and are native only to Japan and the two species have similar characteristics. We assessed potential competition between raccoons and raccoon dogs by comparing feeding habits and habitat use. Both species were captured in Hokkaido, Japan from 2004 to 2017. More raccoons were captured close to agricultural land at the forest periphery (70.1%, 358/511); conversely, more raccoon dogs were captured in the forest core (74.9%, 253/338). Feeding habits were then examined by fecal analysis and stable isotope analyses. Fecal analysis revealed both species to be opportunistic omnivores that consumed easily found food items. However, raccoon feces contained more crops, whereas raccoon dog feces contained more insects, reflecting the different locations in which the species were trapped. Moreover, stable isotope ratios were significantly higher in raccoons than raccoon dogs (Corn has the highest carbon stable isotope (δ C) value, and amphibians and reptiles are high in nitrogen stable isotope (δ N); forest resources such as insects and wild fruits are low in δ C and δ N). We conclude that both species ate similar food types, but their food preferences appeared to differ. Raccoon and raccoon dog habitat use also differed, possibly because the two species inhabited areas where they could easily obtain their preferred foods. Therefore, the current feeding habits and habitat use of raccoons do not appear to overlap sufficiently with those of raccoon dogs to impact the latter. The results of this study, particularly the stable isotope data, may provide a useful precedent for future studies of competition in medium-sized mammals, particularly canids.